1966
DOI: 10.1021/j100881a006
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Study of the Nature of the Hydroxyl Groups on the Surface of Porous Glass

Abstract: The slow dehydration and dehydroxylation of porous Vycor glass was followed by infrared spectroscopic techniques. Two sharp bands at 3748 and 3703 cm-1 and also two shoulders near 3850 and 3650 cm-1 were observed. Dehydroxylation, deuteration, fluoridation, and adsorption experiments showed all absorptions to be due to surface hydroxyl species. The 3748-cm-1 absorption is due to free surface silanol groups. The 3650-cm-1 shoulder is due to OH vibrations perturbed by hydrogen bonding. The 3703-cm-1 band has a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0
2

Year Published

1969
1969
2002
2002

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(30 citation statements)
references
References 0 publications
1
27
0
2
Order By: Relevance
“…In a number of cases it was found that the intensity of the band due to the free silanol groups was essentially unaffected on adsorption of water [29,[36][37][38][39][40][41][42], while in others it definitely decreased [6,[43][44][45][46][47]. In their extensive studies on porous silica glass, Low and Ramasubramanian [17,48,491 show that B-OH groups not only exist on the well-dehydroxylated glass surface but are the main centres of water adsorpttion. A band in the fundamental region at 3,600 cm-1 has been ascribed to molecular water adsorbed on boron.…”
Section: Site Of Adsorptionmentioning
confidence: 99%
“…In a number of cases it was found that the intensity of the band due to the free silanol groups was essentially unaffected on adsorption of water [29,[36][37][38][39][40][41][42], while in others it definitely decreased [6,[43][44][45][46][47]. In their extensive studies on porous silica glass, Low and Ramasubramanian [17,48,491 show that B-OH groups not only exist on the well-dehydroxylated glass surface but are the main centres of water adsorpttion. A band in the fundamental region at 3,600 cm-1 has been ascribed to molecular water adsorbed on boron.…”
Section: Site Of Adsorptionmentioning
confidence: 99%
“…The adsorbents used were Cab-0-Sil silica1, porous glass2, and fully fluoridated porous glass (2). The porous glass was used for most of the work because of the ease of preparing and handling of the samples.…”
Section: Methodsmentioning
confidence: 99%
“…anisole was subjected to freeze-thaw cycles and was distilled in vacuo. Some minor experimental details are given elsewhere (2). Spectra were recorded with a Perkin-Elmer model 621 spectrometer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work has shown that many of the differences in the surface properties of porous glass and pure silica can be attributed to the minority constituents on the glass (1,2). Pure silica is relatively inert, but can be made "active," so that it resembles porous glass in behavior, by impregnating the silica with oxides such as alumina or boria.…”
mentioning
confidence: 99%